2021
DOI: 10.3390/vaccines9060677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Functional Immunity Following Encapsulated Bacterial Infection and Vaccination

Abstract: Encapsulated bacteria such as Streptococcus pneumoniae, Haemophilus influenzae type b and Neisseria meningitidis cause significant morbidity and mortality in young children despite the availability of vaccines. Highly specific antibodies are the primary mechanism of protection against invasive disease. Robust and standardised assays that measure functional antibodies are also necessary for vaccine evaluation and allow for the accurate comparison of data between clinical studies. This mini review describes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…We also applied the Opsonophagocytosis test to assess the in vitro potential protective effects of PspA-based vaccines against pneumococcus strains representing both PspA families. The gold standard in-vitro test for assessing the polysaccharide-base pneumococcal vaccine effectiveness is the Opsonophagocytosis assay [ 16 , 81 ]. Opsonophagocytosis is thought to be considered an important function in the host defense for the elimination of pneumococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also applied the Opsonophagocytosis test to assess the in vitro potential protective effects of PspA-based vaccines against pneumococcus strains representing both PspA families. The gold standard in-vitro test for assessing the polysaccharide-base pneumococcal vaccine effectiveness is the Opsonophagocytosis assay [ 16 , 81 ]. Opsonophagocytosis is thought to be considered an important function in the host defense for the elimination of pneumococci.…”
Section: Discussionmentioning
confidence: 99%
“…This process is started by complement activation in the presence of antibodies that are attached to the surface of pneumococci. Then, using phagocytic cells, pneumococci are swallowed and killed [ 16 , 81 ]. The results showed that the anti-PspA 1-5c+p antibodies act as a good opsonin for killing pneumococcal strains and can attach to the native protein from each PspA clade on the surface of pneumococcal strains representing both PspA families.…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies strongly bound to the pathogen, but their key role is to eliminate the bacteria and protect against infection . Two in vitro functional assays were employed to assess the functional activity of the antibodies and measure the vaccine efficacy, the serum bactericidal antibody (SBA) assay and the opsonophagocytic killing assay (OPKA). Both assays work similarly, whereas, SBA mediates antibody-mediated and complement-dependent killing of the bacteria, OPKA measures antibody-mediated, complement-dependent uptake and killing by phagocytic cells .…”
Section: Resultsmentioning
confidence: 99%
“…OPKA quantifies the opsonic activity of the specific antibodies and the uptake of the bacteria by phagocytic cells, resulting in the death of the bacteria. , The 50% killing of N. meningitidis C is between 1:32 and 1:64 serum dilutions for the DisAF-CRM-Alum group, but human control sera showed a slightly higher protection (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…A key function of CPS targeting vaccines is to elicit antibodies that have opsonophagocytic activity, which has been well defined to be a predictor of protection (Poehling et al, 2006;Ekström et al, 2007;Goldblatt et al, 2010;Prymula et al, 2011;Dagan et al, 2013;Lee et al, 2014) (Figure 2). Indeed, in vitro opsonophagocytic assays are the gold standard for measuring antibody-mediated immunity (Romero-Steiner et al, 1997;Song et al, 2013;Toh et al, 2021). In addition, antibody agglutination activity is a correlate of protection (Bull, 1915), as the establishment of colonization by S. pneumoniae is a critical first step in disease pathogenesis, and antibody agglutinating activity inhibits colonization (Bogaert et al, 2004;Simell et al, 2012) (Figure 2).…”
Section: Antibodies To the Pneumococcal Capsular Polysaccharidementioning
confidence: 99%